SOSIALISASI PENGEMBANGAN APARATUR DESA DALAM PENGELOLAAN ADMINISTRASI DESA - Ahmad Putra Permata Rahmatan; Elvira Suryani; Ainur Rofieq (An-Nizam, 2023)
The background of this research is the lack of optimality of the Village Head in conducting comprehensive data collection on village officials from various aspects of qualifications, competence, work experience, less than optimal in providing direction and coaching continuously as well as technical trainings to improve skills and job performance to the village apparatus so that what is planned is not optimally achieved and less than optimal in evaluating the results of the performance of village apparatus to achieve the desired results better. The village has developed in various forms so that it needs to be protected and empowered so that it becomes stronger, advanced, independent and democratic so that it can create a strong foundation in carrying out governance and development towards a just, prosperous and prosperous society. Administrative management in Village Government is an obligation that must be carried out. With the formation of good village government administration, good governance will be formed, development will run smoothly and social life will be orderly. A good and correct village administration system will create an orderly administration, that is, it can provide easy data and information for the community and for the village government in making policies.